Adherence of College of Education Students towards Prevention of COVID-19 Pandemic Disease - Ibrahim Ologele (IJORER : International Journal of Recent Educational Research, 2023)
The brunt of COVID-19 is currently being felt in all spheres of human endeavor; it has affected the health, economy, education, religion, and overall well-being of all citizens. The study objectives are to investigate whether: (i) Kwara State College of Education students adhere to hand washing; (ii) adherence to receiving a vaccine for prevention of the COVID-19 pandemic; and (iii) to investigate if there is a difference between male and female students adherence towards preventive measures to COVID-19 pandemic. The descriptive research design of the survey type was employed for the study. The study population comprised all students of the College of Education Ilorin. A multi-stage sampling technique was used to select two hundred and fourteen (214) respondents who participated in the study. The study outcome indicated that students of the College of Education adhere to hand washing, not adherence to vaccine collection. There are differences in male and female adherence to preventive measures during the COVID-19 pandemic. Evidence realized from the study also recommends implication for the colleges of education authority to conduct a sensitization program for students on the benefits of adherence to all COVID-19 preventive measures designed by the Centre for Disease Control (CDC) and the World Health Organisation (WHO) on coronavirus disease to protect them as well as their family members against the coronavirus disease.